Design and manufacture of lead-free eco-friendly cement-based piezoelectric composites achieving superior piezoelectric properties for concrete structure applications. (15th June 2023) - Shi, Cheng; Lin, Jinfeng; Ge, Guanglong; Hao, Yali; Song, Jiayue; Wei, Yongqi; Yao, Wu
Abstract: A complex-ion doping strategy fabricates lead-free BCZT ceramic. The excellent properties ( d 33 ∼ 577 pC/N, K t  ∼ 52%, T C  ∼ 110 °C, d ∗ 33 ∼ 620 pm/V, εr  ∼ 1820, tanδ ∼ 0.02) were obtained in BCZT ceramic. The in-situ Raman spectroscopy and PFM were conducted to reveal the mechanisms for the superior properties achieved. BCZT ceramics were manufactured for cement-based piezoelectric composites, including 0–3, 2-2 and 1–3 types. 0–3 type (50% BCZT) showed the properties ( d 33 ∼ 46 pC/N, ε r  ∼ 310 and K t  ∼ 18.1%). 2-2 and 1–3 types exhibited good piezoelectric properties ( d 33 ∼ 285 pC/N, ε r  ∼ 720 and K t  ∼ 33.4% for 2-2 type; d 33 ∼ 238 pC/N, ε r  ∼ 485 and K t  ∼ 29.5% for 1–3 type). Temperature-dependent electrical properties of BCZT-cement composites were systematically explored. Additionally, BCZT ceramic was designed and fabricated for PCD vibration energy harvesting. The output voltage (∼4.9 V) and output power (∼2.4 mW) were obtained. This work underpins the significance of lead-free BCZT ceramic and cement-based piezoelectric composites, and promotes their applications in smart structures. Graphical abstract: The eco-friendly BCZT ceramic with excellent properties can serve as a promising alternative to lead-based materials for application of building and concrete structure fields. Image 1 Highlights: A complex-ion doping strategy fabricates a superior lead-free piezoelectric ceramic (Ba0.85 Ca0.15 )(Ti0.9 Zr0.1 )O3 (BCZT). The 0–3, 2-2 and 1–3 types BCZT/cement composites were manufactured. The piezoelectricity in response to temperature variation was explored by in-situ measurements. Temperature-dependent dielectric constants and dielectric losses of BCZT-cement composites were systematically explored. Output power (∼2.4 mW) was realized by BCZT vibration energy harvesting.